Hubungan Antara Gaya Belajar dan Achievement Motivation Peserta Didik Sekolah Dasar - Mayrisa Undari; Salmiyanti Salmiyanti; Yanti Fitria (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Achievement Motivation can be developed from scratch and cannot be done by itself. Categories that affect Achievement Motivation are those that are influenced by many factors related to other people and students themselves. Learning style is one of the factors that can influence Achievement Motivation. Based on learning style preferences there are visual, auditory and kinesthetic learning styles. In addition to learning styles, it also influences Achievement Motivation. The purpose of this research is to see the relationship between learning style and achievement motivation of elementary school students. The analytical method used is literature study, reviewing or examining various documents published by academics or other researchers related to the subject. The results of the analysis of several previous studies show that learning styles greatly influence Achievement Motivation on academic achievement, so that various strategies are taken to optimize learning styles. while for the most dominant learning style is the visual learning style compared to the auditory learning style.